THE FEATURES OF THE LATE WORKS OF NAGUIB MAHFOUZ (ANALYSIS OF THE NOVELS “THE JOURNEY OF IBN FATTOUMA” AND “WEDDING SONG”) - Zarytovskaya, V.N. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Literaturovedenie, zhurnalistika, 2018)
The article is devoted to the non-linguistic issues of translation of modern Arabic literature into Russian and the problems of its distribution, which the author considers using the example of the novels of the only Arabic-language Nobel laureate in literature Nagib Mahfuz. The study analyzes the evolution of creativity of the Egyptian writer and discusses in detail two of his later novel, translated into Russian language - “The Journey of Ibn Fattouma” and “Wedding song”. The paper demonstrates the correspondence of these works to the European standards of the novel of the late twentieth century and emphasizes their cosmopolitanism as a feature of the late stage of Mahfouz creativity. The author raises the question of why the works of Arab writers deprived of “local color” and following the current trends of world literature remain unclaimed by publishers and readers.